Impacts of De‐NOx system layouts of a diesel passenger car on exhaust emission factors and monetary penalty - Jianbing Gao (Wiley, 2021)
Abstract Automobile emissions are significantly dependent on the after‐treatment system performance, which is partly determined by exhaust temperature. Regarding diesel passenger cars, after‐treatment systems generally include diesel oxidation catalyst (DOC), diesel particulate filter (DPF), and selective catalytic reduction (SCR). The layouts affect their temperature variations because of the heat loss and thermal capacity of tailpipes and after‐treatment systems. As for the original layout of DOC+DPF+SCR, nitrogen oxides (NOx) emissions are the main concerns of diesel vehicle emissions, especially under cold‐start conditions. Ammonia Creation and Conversion Technology (ACCT) system shows excellent performance of reducing cold‐start NOx emissions; additionally, the damage costs of individual exhaust emissions are different greatly, which may change the priority of emission reductions when considering monetary penalty. In this article, the impacts of the after‐treatment system layouts on the exhaust emission reductions were investigated based on a diesel passenger car; additionally, SCR and ACCT systems as the De‐NOx devices were adopted individually in corresponding scenarios; the after‐treatment system layouts were assessed from the viewpoints of both emission factors and monetary penalty. The results indicated that the ACCT system presented much better NOx reduction effectiveness than SCR system over different layouts. NOx reduction efficiency was very sensitive to vehicle operation conditions over the upstream layouts of NOx reduction devices. The layout‐1 of DOC+ACCT+DPF showed the lowest global emission factors from the diesel passenger car. DPF was much easier to achieve regeneration under the original layout conditions due to its shortest distance to the engine. The layout‐2 of ACCT+DOC+DPF had the minimum monetary penalty factor of exhaust emissions from this diesel passenger car.